Gamma radiation in association with moderate training reduce the effects of asthma in mice - Nayara Alves Severo; Cilene Souza Barreto; Maria de Lourdes Meirelles Noviello; João Aguiar Nogueira Batista; Rosiane Resende Leite; Arno Heeren de Oliveria (Brazilian Journal of Radiation Sciences, 2022)
Ionizing radiation has been used for the treatment of various diseases for over a century, including chronic inflammatory diseases and cancer. The relationship between radiation and asthma are contradictory; while some authors associate radiation exposure with the development of the disease, others report an attenuation of asthma in response to radiation. Asthma is a chronic inflammatory disease and represents a worldwide public health problem with a high number of deaths. In the present study, we have conducted an investigation of the effects of radiation with 10 doses of 0.5Gy of Co60 and/or moderate lung training of mice with ovalbumin-induced asthma. For this purpose, we have compared six experimental groups of mice: 1-Saline (non-irradiated, sedentary and saline); 2- IR (irradiated and sedentary); 3- OVA (non-irradiated, sedentary and asthma); 4- OVA+IR (irradiated, asthma and sedentary); 5- OVA+IR+MT (irradiated, asthma and moderate training -TM); 6- OVA+MT (asthma and moderate training). The results indicate that radiation and moderate training reduced inflammatory parameters significantly both in BALF cells and in mucus production, thus attenuating the asthma symptoms.